2019
DOI: 10.1177/1099636219836645
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects aviation fluids have on the flatwise compressive strength of Nomex® honeycomb core material

Abstract: One of the disadvantages of honeycomb sandwich structure is that they are prone to fluid intrusion. The purpose of this study is to determine if the structural properties of honeycomb core are affected by contact with a fluid. The test specimens were manufactured of fiberglass prepreg for the facesheets and Nomex ® honeycomb core for the core material in accordance with ASTM C-365/365M. Test specimens were soaked in several different kinds of fluids, such as aircraft fuel, turbine engine oil, hydraulic fluid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
(87 reference statements)
0
7
0
1
Order By: Relevance
“…Following that, it is a crushing stage with the load being increased. 7,27 The test is terminated at a displacement of 8 mm and the specimen is not compressed to the densification stage because of the mean compressive strength was the main focus in this study.
Figure 5.The typical experimental load-displacement curve of PPHC under flatwise compression: (a) the full curve; (b) the local amplification of curve.
…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…Following that, it is a crushing stage with the load being increased. 7,27 The test is terminated at a displacement of 8 mm and the specimen is not compressed to the densification stage because of the mean compressive strength was the main focus in this study.
Figure 5.The typical experimental load-displacement curve of PPHC under flatwise compression: (a) the full curve; (b) the local amplification of curve.
…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…There are many studies that report relationships between the moisture content and composite structures [8]. It has been found that the delamination area and the number of transverse cracks of wet specimens are smaller, due to the buffering effect of water absorption [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hasil ini juga diperkuat dengan jurnal penelitian [8] dimana spesimen yang lebih kering menghasilkan data yang lebih besar. Pengeringan menggunakan suhu ruang kurang efektif digunakan dikarenakan masih memungkinkan adanya sisa uap air/solvent (moisture) yang masih terjerembap pada core.…”
Section: Hasil Dan Pembahasanunclassified